Kinetic asymmetry in the gel-liquid crystalline state transitions of DDAB vesicles studied by differential scanning calorimetry - Feitosa, Eloi [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
Didodecyldimethylammonium bromide (DDAB) (1.0 mM) vesicles in water were investigated by differential scanning calorimetry (DSC) to highlight the existing kinetic asymmetry in the gel-liquid crystalline (LC) state transitions. The experiments were performed in the range of temperature, scan rate and pre-scanning time 5-45 degrees C, 15-90 degrees C/h and 0-16 h, respectively, in the up- and down-scanning modes. Depending on the input parameters and number of heating-cooling cycles, the DSC thermograms exhibit a sharp peak, a broad band or a flat shape. A melting temperature T(m) = 15.6-16.0 degrees C, given by the peak position, was obtained independently of the scan rate used in the up-scanning mode. The data reveal that DDAB vesicles exhibit much slower kinetics for the LC to gel state than for the opposite transition. Such an asymmetry is supported by: (a) the absence of peak for shorter pre-scanning times but longer scan rates, (b) the increasing intensity of the DSC peak with increasing pre-scanning time and decreasing scan rate, and (c) the complete absence of peak in the down-scan mode. Longer pre-scanning time, however, yields crystal precipitates due to a Krafft phenomenon, which also reduces the peak intensity. The overall results depend on whether the sample is fresh or not, that is, after some heating-cooling cycles, the melting peak requires a longer pre-scanning time to be detected. The kinetic asymmetry explains, for example, the lack of any DSC melting peak reported for "non-fresh" DDAB vesicles, which was as yet unexplained. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: DDAB; DSC; Cationic vesicle; Melting temperature; Thermal hysteresis; Krafft point